2020
DOI: 10.1177/2331216520932467
|View full text |Cite
|
Sign up to set email alerts
|

Perception of One’s Own Voice After Hearing-Aid Fitting for Naive Hearing-Aid Users and Hearing-Aid Refitting for Experienced Hearing-Aid Users

Abstract: Dissatisfaction with the sound of one’s own voice is common among hearing-aid users. Little is known regarding how hearing impairment and hearing aids separately affect own-voice perception. This study examined own-voice perception and associated issues before and after a hearing-aid fitting for new hearing-aid users and refitting for experienced users to investigate whether it was possible to differentiate between the effect of (unaided) hearing impairment and hearing aids. Further aims were to investigate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The phenomenon ampclusion ( Painton, 1993 ) describes how the hearing-aid wearers’ perception of their own voice is changed, not only by the amplification, but also by altered auditory feedback arising from closed-dome hearing aids occluding the ear canal. A recent study found that experienced hearing-aid users rated their voice as being more dominating after receiving new hearing aids, even more so than a group of participants receiving their first hearing aids ( Hengen, Hammarström, & Stenfelt, 2020 ). In the current study, the hearing aids were programmed with active occlusion cancellation, which reduces the gain upon detecting the wearer's own voice, hence trying to compensate for the ampclusion and occlusion effects experienced while talking.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon ampclusion ( Painton, 1993 ) describes how the hearing-aid wearers’ perception of their own voice is changed, not only by the amplification, but also by altered auditory feedback arising from closed-dome hearing aids occluding the ear canal. A recent study found that experienced hearing-aid users rated their voice as being more dominating after receiving new hearing aids, even more so than a group of participants receiving their first hearing aids ( Hengen, Hammarström, & Stenfelt, 2020 ). In the current study, the hearing aids were programmed with active occlusion cancellation, which reduces the gain upon detecting the wearer's own voice, hence trying to compensate for the ampclusion and occlusion effects experienced while talking.…”
Section: Discussionmentioning
confidence: 99%